Assessment of milk yield, composition and fatty acid profiling of Murrah buffaloes supplemented with cumin powder during hot dry and hot humid seasons under field condition - Kumar, Gaurav; Singh, Sohan Vir; Bhalakiya, Nikita; Ukey, Apeksha; Kumar, Rajkumar (Indian Journal of Dairy Science, 2026)
During the course of six months and encompassing two seasons, this field study was conducted on lactating Murrah buffaloes under the Framer FIRST project to assess the impact of cumin powder supplementation on milk production performance during hot dry and hot humid seasons. Twelve lactating Murrah buffaloes were selected from Kathura village of Sonipat district of India and equally divided into two groups i.e. treatment (cumin supplemented) and control group. Throughout the study, the milk production from each animal was recorded and the composition of the milk samples was also examined. Further milk fat was analysed for fatty acid composition. The results of the study showed that supplementation of cumin during both the seasons significantly (P